Assessment of the Capability of TiungSAT-1 Satellite Data for Mapping Chlorophyll Distribution - Mohd., Mohd. Ibrahim Seeni (Astronautic Technology (M) Sdn. Bhd., 2003)
The capability of TiungSAT-1 Multispectral Earth Imaging System (MSEIS) satellite data for mapping chlorophyll distribution was assessed for the coastal areas of Muar, Johor by using the green band 3 (0.50 â€“ 0.59Âµm), acquired on 29 July 2001. Sea viewing Wide Field of view Sensor (SeaWiFS) data using the SeaWiFS default chlorophyll-a algorithm (OC4V4) was used to derive chlorophyll-a in the study area. The bands used are band 2 (443nm), band 3 (490nm), band 4 (510nm) and band 5 (555nm). The digital numbers (DN) of TiungSAT-1 data were converted to reflectance values by using internal average relative reflectance (IARR). A plot of SeaWiFS chlorophyll-a versus reflectance values from TiungSAT-1 data was made. The plots show that there is no correlation between reflectance values from TiungSAT-1 data and chlorophyll-a values from SeaWiFS data. This is due to the unavailability of the blue band and the stripping effects in the TiungSAT-1 data. This indicates that the TiungSAT-1 satellite data is not useful in ocean colour studies to derive chlorophyll data.